EDUKASI SADAR (SEMANGAT MENGATASI DAN DETEKSI RESIKO) DALAM MEMBANGUN MASYARAKAT SAYANG GINJAL - Kheniva Diah Anggita; Anisa Fadilah; Rifqi Aulia Zaim; Prima Yoselina (Ensiklopedia Research and Community Service Review, 2025)
Sikapak Barat village, located in the North Pariaman sub-district, has the highest number of hypertension and diabetes mellitus cases among the six villages served by the Sikapak Public Health Center. The majority of its residents are farmers and laborers with demanding routines, who often rely on packaged and canned energy drinks to combat fatigue. While these beverages are seen as a way to stay refreshed and boost energy, excessive long-term consumption can lead to various negative health consequences, including kidney disease. This community service project provides an alternative strategy to control the risk factors for kidney disease. This involves conducting blood pressure and blood sugar screenings and providing support on overcoming and detecting risks education using a Focus Group Discussion (FGD) method, to foster a "Caring for Your Kidneys" community. The primary objective is to empower residents to become more aware of and understand the importance of maintaining their kidney health. It is expected that sufficient knowledge will enable the community to take preventive measures, such as managing their blood pressure and blood sugar levels, and adopting a healthy lifestyle. The SADAR education using the FGD method proved to be effective, as evidenced by a significant change in knowledge between the pre-test and post-test scores (t = -6.361, p 0.05). It is hoped that the people of Sikapak Barat village will be more active in understanding and preventing the risks of kidney disease and be able to perform early detection independently or with the assistance of medical personnel. Keywords:  Hypertension; Diabetes Mellitus, Kidney; Education; Focus Group Discussion